2019
DOI: 10.3390/ijerph16245029
|View full text |Cite
|
Sign up to set email alerts
|

Development of Physical Performance Tasks during Rapid Growth in Brazilian Children: The Cariri Healthy Growth Study

Abstract: Growth and physical performance scores were studied around three years of attainment of peak height velocity (PHV). We aimed to estimate the age at peak velocity, or at peak rate, in physical performance tasks, and sex-differences when aligned by biological age. A total of 131 boys and 123 girls, 8 to 14 years of age were recruited from the Cariri region of Brazil. A mixed longitudinal design was used with four overlapping age cohorts: 8, 10, 12, and 14 years, followed for three years, with measurements perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…The number of players used to estimate peak spurts was never higher than 17 participants. Similar difficulties have been reported in other studies with non-athletic adolescents [ 2 , 11 , 13 ]. Second, this study used a mixed-longitudinal design with only three data waves per cohort, which may have limited the estimation of height and muscular strength spurts in some players.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The number of players used to estimate peak spurts was never higher than 17 participants. Similar difficulties have been reported in other studies with non-athletic adolescents [ 2 , 11 , 13 ]. Second, this study used a mixed-longitudinal design with only three data waves per cohort, which may have limited the estimation of height and muscular strength spurts in some players.…”
Section: Discussionsupporting
confidence: 89%
“…Comparable results were only available for non-athletic boys from Portugal and Brazil. Guimarães et al [ 10 ] identified peaks in handgrip strength coincident and 12 months after-PHV (intensity = 6.1 and 6.1 kgf·year −1 , respectively), whereas Silva et al [ 11 ] found it 9 to 12 months also after-PHV (intensity = 8.4 and 8.2 kgf·year −1 , respectively). Similar timings, after-PHV, were reported in other populations of adolescent males, although using different static strength markers [ 2 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in Belgian twins, VO 2peak coincided with APHV (Geithner et al 2004), whereas in Canadian boys VO 2max occurred $6 months after APHV (Mirwald et al 1981). The peak spurt in standing long jump occurred 6 months before APHV in Brazilian boys (Silva et al 2019), was coincident with APHV in Canadian boys (Ellis et al 1975), but was found to plateau from APHV to 12 months post-PHV in both Spanish boys (Yag€ ue and De La Fuente 1998) and in Belgian boys (Philippaerts et al 2006).…”
Section: Introductionmentioning
confidence: 94%